X-Ray Crystallography of Tetracycline, Doxycycline and Sancycline - Heinemann, Frank Wilhelm; Leypold, Clemens; Roman, Cyprian R.; Schmitt, Matthias O.; Schneider, Siegfried (Journal of Chemical Crystallography, 2013)
Although the packing of the three title compounds in the respective crystals is different, the geometries of the molecular framework are nearly the same as the one shown for the sancycline cation. A comparison of experimentally determined bond lengths with calculated Wiberg-Bond orders provides evidence that only one tautomer is present in the crystal..
Keywords: Molecular and crystal structures; Tetracycline; Doxycycline; Sancycline; Wiberg-bond order